Flavonoids of Melilotus indica - H. El-Sayed, Nabil; S. Ishak, Moheb; J. Mabry, Tom (Asian Journal of Chemistry, 2010)
In the present note, some flavonoids were extracted and isolated from Melilotus indica plant.